Levels of soil water on herbaceous cotton yield - Oliveira, Francisco Assis de; Campos, Tarcísio Gomes da Silva; Santos, José Wellington dos; Maciel, Marcel José Queiroga (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was carried out on an afluvial soil of the São Gonçalo irrigation project, in Sousa, PB, Brazil, to determine the effects of 45, 35, 25, 15 and 0.5% levels of available soil water on cotton (Gossypium hirsutum L.r. latifolium Hutch.) anual yield. Soil water availability levels did not alter cotton production, but the culture prooved to be more sensitive in the period from blossoming up to ripe ball than in the flowering stage, with significant yield decrease. The level of 0.5% of available soil water did not signiflcantly affect cotton yield, but reduced irrigation frequency by 50%.